Study on the Adsorption and Activation Behaviours of Carbon Dioxide over Copper Cluster (Cu4) and Alumina-Supported Copper Catalyst (Cu4/Al2O3) by means of Density Functional Theory - Nguyen Thi Thu Ha; Van Thi Minh Hue; Bui Cong Trinh; Nguyen Ngoc Ha; Le Minh Cam (Journal of Chemistry)
The adsorption and activation of carbon dioxide over copper cluster (Cu4) and copper doped on the alumina support (Cu4/Al2O3) catalytic systems have been investigated by using density functional theory and climbing image nudged elastic band. The adsorption energies, geometrical configurations, and electronic properties are analysed. The results show the strong chemical interaction between the copper cluster and the alumina support. Both the Cu4 cluster and Cu4/Al2O3 systems have a high adsorption ability for CO2, and the adsorption process is of chemical nature. The role of the alumina support in the adsorption and activation of CO2 has been addressed. The calculated results show that the “synergistic effect” between Al2O3 and Cu4 is the key factor in the activation of CO2.